Treatment strategies for unresectable locally advanced non-small cell lung cancer in the real-life ESME cohort. (December 2021) - Girard, Nicolas; Perol, Maurice; Simon, Gaëtane; Audigier Valette, Clarisse; Gervais, Radj; Debieuvre, Didier; Schott, Roland; Quantin, Xavier; Coudert, Bruno; Lena, Hervé; Carton, Matthieu; Robain, Mathieu; et al.
Highlights: In a multicenter, nation-wide cohort of 8514 consecutive patients with advanced or metastatic lung cancer, 736 patients had unresectable locally advanced NSCLC. OS rates at 24 months were similar -–55.3% and 53.2% respectively - for concurrent and sequential chemoradiotherapy. Clinical outcomes were actually higher than those reported in landmark clinical trials. Abstract: Background: Cisplatin-based chemotherapy administered concurrently to thoracic radiation therapy is the recommended treatment for fit patients with unresectable stage III NSCLC. The aim of this study was to describe patient profiles and clinical outcomes for the different treatment strategies in a real-word setting. Methods: The epidemio-strategy and medical economics (ESME) database for advanced and metastatic lung cancer is a French, national, multicenter, observational cohort. Out of 8514 Patients, 822 patients with unresectable locally advanced NSCLC in 2015-016 were selected (mean age, 65.3 years; male gender, 69%; performance status 0–1, 77%; smokers or former smokers, 89%). Results: Treatment was initiated for 736 (90%) of patients (concurrent chemoradiotherapy, n = 283; sequential chemoradiotherapy, n = 121; chemotherapy alone, n = 194; radiotherapy alone, n = 121; targeted therapy alone, n = 8; other, n = 9). Compared to the other treatment strategy groups, patients with radiotherapy alone appeared the most fragile (e.g. higher age, lower body weight or higher frequency of chronic obstructive pulmonary disease). OS rates at 12 and 24 months were 79.5% (95% CI, 73.4–84.3) and 55.3% (95% CI, 44.9–64.5) for concurrent chemoradiotherapy, and 64.3% (95% CI, 52.8–73.8) and 53.2 (95% CI, 33.2–69.6) for sequential chemoradiotherapy. Conclusions: Real-world evidence shows that concurrent chemoradiotherapy is administered to the most fit patients with non resectable locally-advanced NSCLC. Clinical outcomes are actually higher than those reported in landmark clinical trials, which suggests that an optimized and individualized selection of patients allows for prolonged survival. Long-term outcomes are similar after sequential or concurrent chemoradiotherapy.